Pervasive sensing system for healthcare - Chay, Nan Jie. (2013)
The increasing aging population imposed a great challenge in the healthcare facilities. As these elderly need more intensive care, the call for physical monitoring from the caregivers is required. This problem can be alleviated by using a Wireless Body Area Network (WBAN) sensing system for remote, continuous, automated, and unobtrusive monitoring of activities to support healthcare facilities. With the combination of accelerometer, gyroscope and magnetometer, it enables a wide range of motion aware and motion controlled applications such as Sleep Monitoring System to detect body position during sleep. Sleep plays an important role in the well being of human and recovery of a patient. Inadequate and irregular sleeping are related to diseases such as depression and diabetes. Monitoring the body position and movement helps in determining sleep quality and irregular sleeping patterns.